Determinants of Tax Avoidance in Mining Companies 2018-2022 - Aissyiah, Putri Mafazh; Nurlaela, Siti; Chomsatu, Yuli (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The goal of this study was to look at how profitability, leverage, sales growth, institutional ownership, and independent commissioners influence avoidance of taxes. The secondary data source was financial statements from mining businesses that were listed on the Indonesia Stock Exchange (IDX) between 2018 and 2022. For the study, 18 mining companies from the same time period were chosen using purposive selection. The SPSS version 21 was utilized for data analysis, which included multiple linear regression. According to the findings, while leverage and sales growth had no influence on tax avoidance, institutional ownership and the presence of independent commissioners did.